Norvancomycin plasma concentration monitoring in hemodialysis patients with end stage kidney disease: A retrospective cohort study. (28th March 2023) - Du, Liying; Huo, Liman; Hou, Juan; Zhou, Xiajin; Liu, Mingfeng; Guo, Teng; Wang, Wei; Chen, Huihui; Chen, Xinran
Abstract: Blood concentration monitoring plays an important role in the rational use of norvancomycin. However, the reference interval for the norvancomycin plasma concentration in the treatment of infections in hemodialysis patients with end stage kidney disease is undefined. To determine the safe and effective interval for the norvancomycin plasma trough concentration, 39 patients treated with hemodialysis and norvancomycin were analyzed retrospectively. The norvancomycin plasma concentration before hemodialysis was tested as the trough concentration. The associations of the norvancomycin trough concentration with efficacy and adverse reactions were evaluated. No norvancomycin concentration above 20 μg/mL was detected. The trough concentration, but not the dose, had a significant effect on the anti‐infectious efficacy. Compared with the low norvancomycin trough concentration group (<9.30 μg/mL), the high concentration group (9.30–20.0 μg/mL) had improved efficacy (OR = 15.45, p < 0.01) with similar side effects (OR = 0.5417, p = 0.4069). It is beneficial to maintain the norvancomycin trough concentration at 9.30–20.0 μg/mL to achieve a good anti‐infectious effect in hemodialysis patients with end stage kidney disease. Plasma concentration monitoring provides a data basis for the individual treatment of infections with norvancomycin in hemodialysis patients. Abstract : In this study, we collected 39 hemodialysis patients with end stage kidney disease and infection, and investigated the significance of the norvancomycin plasma concentration and its correlation with clinical outcomes, to study the safe and effective reference interval of the norvancomycin trough concentration. We hope it can provide a data basis for the rational application of norvancomycin and individual therapy in hemodialysis patients with end stage kidney disease.